2017
DOI: 10.3178/hrl.11.65
|View full text |Cite
|
Sign up to set email alerts
|

Estimating regional climate change uncertainty in Japan at the end of the 21st century with mixture distribution

Abstract: Abstract:To facilitate accurate assessments of the regional impacts of global warming, and make informed decisions about appropriate measures to mitigate them, detailed global warming projections with uncertainties are needed. The Ministry of Environment of Japan and the Japan Meteorological Agency performed 21 different multi-scenario and multiensemble experiments in Japan using the regional climate model MRI-NHRCM with a horizontal resolution of 20 km.To estimate the total range of uncertainty due to natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The Finite Element/volumE Sea-ice Ocean Model (FESOM) is the ocean-sea-ice component of the coupled Alfred Wegener Institute Climate Model (AWI-CM; . It works on unstructured triangular meshes for both the ocean and sea-ice modules Wang et al, 2008;Timmermann et al, 2009). FESOM version 1.4 (Wang et al, 2014;Danilov et al, 2015) is employed in this study and all the CMIP6 simulations as well.…”
Section: A1 Awi-fesommentioning
confidence: 99%
“…The Finite Element/volumE Sea-ice Ocean Model (FESOM) is the ocean-sea-ice component of the coupled Alfred Wegener Institute Climate Model (AWI-CM; . It works on unstructured triangular meshes for both the ocean and sea-ice modules Wang et al, 2008;Timmermann et al, 2009). FESOM version 1.4 (Wang et al, 2014;Danilov et al, 2015) is employed in this study and all the CMIP6 simulations as well.…”
Section: A1 Awi-fesommentioning
confidence: 99%
“…The IPCC's RCP8.5 climate change scenario assumes a CO 2 partial pressure increase to 905 × 10 -6 Pa Pa -1 by 2100. Temperature in Japan was assumed to rise by 3.8 ± 0.9 K in spring (March-May), by 4.1 ± 0.6 K in summer (June-August), by 4.5 ± 0.8 K in autumn (September-November), and by 4.8 ± 1.0 K in winter (December-February) on the Pacific side of eastern Japan, where the Kawaraya field is located (Japan Meteorological Agency (JMA) 2017; Wakamatsu et al 2017).…”
Section: Forecasted Rice Yield and Soil N Kinetic Changesmentioning
confidence: 99%
“…RCP8.5 is a high radiative forcing pathway. In the models assessed here, by 2100 the multiple-model average greenhouse gas concentration is 985 ± 97 ppm (CO 2 equivalent) and the range of global surface temperature change (2081-2100 average relative to 1986-2005 average) is 2.6-4.7 K. In Japan, the mean temperature is predicted to change by 4.5 K and will be greater at the higher latitudes, and the frequency of anomalous warm periods will increase by 2100 (JMA 2017;Murata et al 2015;Sasaki et al 2012;Wakamatsu et al 2017). Both the quantity and quality of many agricultural products are expected to decline, and production areas will shift.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the annual mean surface air temperature over Japan has increased at a rate of 1.19 • C/100 years, faster than the global average [31]. Annual mean air temperatures in Japan were projected to rise by 1.1 ± 0.4 • C and 4.4 ± 0.6 • C under the RCP2.6 and RCP8.5 scenarios at the end of the 21st century, relative to the end of the 20th century [32]. Although the warming impacts on the fishery species around Japan were mentioned in the report from the Ministry of Agriculture, Forestry and Fisheries [33], little information exists on the snow crab.…”
Section: Introductionmentioning
confidence: 99%